Cretaceous faunas from Zululand and Natal, South Africa. Texasia cricki Spath, 1921 (Cephalopoda: Ammonoidea) an early Santonian marker fossil from the Mzamba Formation of the Eastern Cape Province - Kennedy, William James; Klinger, Herbert Christian (Evolutionary Studies Institute, University of the Witwatersrand, 2013)
The type material of ‘Gen. nov. (Muniericeras?)’ cricki Spath, 1921, from the Santonian part of the Mzamba Formation , Eastern Cape Province, is revised, and referred to Texasia Reeside, 1932, of which Lehmaniceras Collignon, 1966 is a subjective junior synonym. Lehmaniceras sornayi, L. acutum, L. macer, L. pingue, L. ultimum and possibly L. gracile of Collignon, 1966, originally described from Madagascar, are further synonyms, as is Barroisiceras umzambiensis van Hoepen, 1968, which is based on a single specimen from Mzamba. The species occurs in the lower part of the Zone of Texanites hourcqi in Madagascar, confirmed here as lower, rather than middle, Santonian.
Keywords: ammonites; Texasia; Cretaceous; Santonian; Mzamba Formation; South Africa; Madagascar